Shariah principles in the procurement of buildings and infrastructure works - Abdul Rashid, Khairuddin; Mohd Fauzi, Puteri Nur Farah Naadia; Hasan, Sharina Farihah (Kolej Universiti Islam Antarabangsa Selangor, 2017)
The construction sector contributes significantly to the economy in three areas: its contribution to the GDP, in employment and its upstream and downstream linkages with other sectors of the economy. However, procurement of building and infrastructure works is yet to embrace the concept of Shariah compliant. Any effort towards making the procurement processes Shariah compliant would go a long way in transforming the country’s construction sector to be in compliance with the Shariah. Consequently, a study to review key Islamic principles of al-muamalat related to construction procurement and assessing their applicability in the procurement of building and infrastructure works was carried out. The study used a combination of literature review and intensive discussions with 4 academics specializing in the Shariah and construction works’ contracts. The outcome of the study identified key Shariah principles of al-muamalat and identified how they could be applied in the procurement of building and infrastructure works. The study’s outcome is considered significant as it contributes towards further and deeper understanding of the concept Shariah compliant construction procurement and increasing the prospect of its application in future projects.